The backpackers' “round the world” trip, standardised journey? - Brenda Le Bigot (Via@)
At times portrayed as a dissenter against mass tourism, the backpacker is at the same time described as being bound to his own illusions of freedom and reduced to use pre-determined routes and accommodation. Based on the observation of a gap between the backpacker’s ideals and his practices, the article examines the standardisation of backpacking by studying an emblematic subgroup of this type of journey: backpackers on a “round the world” trip. Through the use of a sample group of profiles which turn out to be as diverse as backpackers are in general, the survey carried out in Thailand by means of questionnaires and interviews enable us to examine the standardisation of routes and the stakes surrounding the planning of the trip. The article reveals that routes are structured by the aviation network and that they are strongly standardised in certain areas of the world, such as in Southeast Asia, where enclaves and “beaten tracks” are plentiful. Planning still appears to be hardly framed by commercial offers, and depends largely on the individual project of the backpacker on a “round the world” trip, which we particularly interpret here according to the relation to work. The relation to place which is produced by these